(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The partial discharge analysis of nanostructure mineral oil under dc voltages based nano mineral oil finished by the accumulation of surface modified SiO2 nano particles with nano structure. The nano fluid of %wt concentration of the mineral lubricant is prearranged in the laboratory. The PD nanostructure was deliberate and measured for partial discharge magnitude, positive dc PD inception voltages, negative dc PD inception voltages, positive &negative dc PD amplitude, and PD signals with increasing voltages. IEC principles are used for testing the experiment. The results of nanostructure mineral oil is linked with speculative present mineral lubricant which is used as the primary oil for nano mineral oil and sio2nano particles of mineral lubricant. The secondary nano structured mineral oil results exposing concentrated PD amplitude, pulse signals with the untreated mineral oil and silica added mineral oil.